Comparative effectiveness of 50g glucose challenge test and risk factor based screening in detection of gestational diabetes mellitus in Ibadan, Nigeria. (2015)
Context: Gestational diabetes mellitus (GDM) complicates 3-5% of pregnancies. Prompt diagnosis helps to prevent its subsequent complications and one-step effective screening method is desirable for our environment. Objective: To compare the effectiveness of 50g glucose challenge test (GCT) with risk factors alone in screening for GDM. Study Design: Prospective study of booked, consenting pregnant women with no previous history of diabetes mellitus. Fasting sample of venous blood was obtained for plasma glucose, followed by administration of SOg oral glucose and collection of blood sample an hour later. The process was repeated after a week using 7Sg oral glucose; each patient serving as her own control. Threshold blood glucose of 140mg/dl was used for both post-ingestion tests. Statistical analysis was done using SPSS version 17. Results: All the seventy-nine study participants completed the 2 arms. Mean maternal and gestational ages at recruitment were 30.8+1.2 years and 24.2+1.6 weeks respectively. Among the respondent, 3S( 44.3%)were nulliparous while24(30.3%) had positive risk factors for GDM. The 50g GCT was abnormalin 10 patients (12.7%) while GDM was confirmed in 2 patients giving an incidence rate of2.5%. The 50g GCT was normal in 89.6% of women withnormat75g OGTT and it was more predictive of GDM (Positive Predictive Value, PPV -20%) compared to risk factors only (PPV-11.1 %). Conclusion: Using 50g GCT will enhance selection of patients for confirmatory test for GDM as compared to risk factors alone. It would therefore be of great benefit in this environment.